ARDUINO UNO BASED AUTOMATIC DESIGN TO BUILD WINE DRINKING TOOL USING SOIL MOISTURE SENSOR - Akbar Sujiwa; Oktavianus Hadiwikarta (BEST, 2020)
The development in this era is increasing, humans expect a tool or technology that can help human work, because now technology has become a human need. Therefore, a device that can do watering the wine is made automatically. This tool aims to replace manual work to be automatic. The benefits that can be obtained from this tool is that it can facilitate human work in watering grapes. This tool uses a soil moisture sensor which functions as a soil moisture detector and sends commands to Arduino uno to turn on the relay driver so that the pump can flush water according to soil needs automatically. The making of this final project is done by designing, creating and implementing system components including Arduino uno as a controller, relay drivers for turning on and off the water pump, LCD (Liquid Cristal Display) to display soil moisture values. The results of the research prove that the tool made can function properly and can be developed as expected. The tool can water the vine when the soil humidity is below 50%, and turn off the pump when the soil moisture is above 50%.